1992
DOI: 10.1007/bf01211802
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase enhances the activity of Adriamycin in breast cancer models in vitro and in vivo

Abstract: Summary.The effect ofhyaluronidase and a combination of hyaluronidase with Adriamycin was investigated on several breast cancer models in vitro and in vivo. In vitro enzyme treatment (using concentrations up to 80 000 IU/ 1) of routine (MXT-, MXT -+, and MXT +) and human (MCF-7, ZR-75-1 and T-47-D) breast cancer cell lines did not inhibit tumour cell proliferation (measured by a kinetic crystal violet assay) in either case. Although highdose hyaluronidase (1.2 x 106 IU/kg) was ineffective, when administered pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…The enzyme hyaluronidase degrading hyaluronan is reported, in phase I and II trials, to prevent regrowth of various tumour types and to improve clinical outcome when given adjuvant to chemotherapy (Baumgartner, 1987;Maier and Baumgartner, 1989;Smith et al, 1997), and delays the growth of human breast cancer xenografts compared with doxorubicin given alone, when given as a pretreatment to doxorubicin (Beckenlehner et al, 1992). However, it has been reported that such pretreatment may induce drug resistance (Chang, 2001).…”
mentioning
confidence: 99%
“…The enzyme hyaluronidase degrading hyaluronan is reported, in phase I and II trials, to prevent regrowth of various tumour types and to improve clinical outcome when given adjuvant to chemotherapy (Baumgartner, 1987;Maier and Baumgartner, 1989;Smith et al, 1997), and delays the growth of human breast cancer xenografts compared with doxorubicin given alone, when given as a pretreatment to doxorubicin (Beckenlehner et al, 1992). However, it has been reported that such pretreatment may induce drug resistance (Chang, 2001).…”
mentioning
confidence: 99%
“…Our patient was specifically treated with a purified preparation of hyaluronidase derived from recombinant human deoxyribonucleic acid (DNA) called Hylenex ® . The method of action of intralesional hyaluronidase in these cases deserves further investigation, though it has been used as a successful adjuvant therapy in the treatment of various epithelial and mesenchymal cell-driven processes including dermatofibrosarcoma protuberans prior to excision, bladder cancer, breast cancer and Kaposi's sarcoma [23][24][25][26] . Our success in this case further suggests a role for hyaluronidase in the treatment of papular mucinosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some bacteria such as Streptococcus pyogenes and Clostridium perfringens produce hyaluronidase (Ohya T., 1970). Hyaluronidase resists spreading of venoms and virulence of bacteria and may play a role in cancer metastasis and angiogenesis (Beckenlehner K., 1992). Therefore it is used in medicine (Schomberg D., 1991).…”
Section: Introductionmentioning
confidence: 99%